Feeding zinc biofortified sorghum stover decreases zinc deficiency in sheep - GIRIDHAR, K; GOWDA, N K S; PAL, D T; KRISHNAMOORTHY, P; JOSEPH, R F; DEY, D K; SHUKLA, A K (The Indian Journal of Animal Sciences, 2021)
Study was conducted to evaluate feeding zinc (Zn) biofortifed sorghum stover to ameliorate Zn deficiency in sheep. The sorghum stover grown on zinc fortified soil was used for experimental feeding to Zn deficient sheep and compared with feeding unfortified stover as control for 120 days period. Application of zinc sulfate to soil @ 25 kg/ha increased the sorghum stover yield by 4.20 tonnes/hectare and enhanced the Zn content of stover by 14.4 ppm. Higher Zn intake in sheep fed biofortified stover resulted in significantly higher apparent gut absorption of Zn (37.2 vs 30.1%) and higher bioavailable Zn (6.12 vs 3.20 mg). Feeding Zn biofortified sorghum stover resulted in increase in plasma Zn content and the level was significantly higher after 3rd month of feeding the biofortified stover. The average plasma Zn content was significantly higher in group fed biofortified sorghum stover (1.14 vs 0.90 ppm). This resulted in higher Zn content in liver (150 vs 130 ppm, DM), enhanced activity of plasma superoxide dismutase (15.5 vs 10.3 Units/min) and better immune response to Peste des petits ruminants (PPR) vaccination (76.8 vs 59.5% inhibition). The results of this study prove that Zn fertilization of deficient soils is a practical method to increase the Zn content of stover and feeding of such biofortified stover can ameliorate the Zn deficiency in sheep.